Verità Potere Giustizia. Prolegomeni a una lettura di “Effetto Sicilia” di Carlo Alberto Madrignani - Marino, Mario (Studia Romanica Posnaniensia, 2014)
The paper discusses the final work (Effetto Sicilia, 2007) of one of the most significant scholars of Italian modern novel, Carlo Alberto Madrignani (1936-2008), by focusing on the interaction between three historical, literary and intellectual elements: 1) the scientifically rigorous civil tradition Madrignani belonged to, 2) the peculiar realistic code which arose in Sicily after the Italian unification and has been constantly renewed till our times in an astonishing, problematic continuity, 3) the Italian conflictual and dramatic modernity which triggered the birth of Sicilian modern novel and at the same time is provoked by the ‘outrageous’ kind of literature. The key issues of both the literary tradition and Italian modern history are 1) the violent and ambiguous sociopo litical control on collective and individual bodies (especially female), 2) the ambivalence of myth 3) the contradiction between individual and collective expectations on one side and institutions on the other 4) the uncertainty of trutdthe dissolution of theological and religious compensations.